Women in charge: Contemporary Inuit artists - Faldini, Luisa (Società Italiana di Antropologia Culturale (SIAC), 2015)
Review of Women in charge. Artiste inuit contemporanee. Recensione di Women in charge. Artiste inuit contemporanee.